Cluster Policy in the Russian Federation: A Case Study of Industrial Clusters - Rodionova, Irina; Krejdenko, Tatiana; Mądry, Cezary (Quaestiones Geographicae, 2018)
The article describes cluster policy in the Russian Federation regarding industrial clusters. In the first part, the authors explain the definitions of basic concepts related to clusters that are used in Russia, the features of cluster policy in the light of European experiences, and bring closer the Russian literature on the subject. In the second part, they distinguish and describe five stages of cluster policy in Russia. In the third part, they present basic quantitative data describing clusters in Russia, including their spatial diversification, the number of entities creating clusters, employment, etc. A particular role of the state in creating clusters and subsequent cluster policy programs is described, paying attention to their low efficiency.